Tracheostomy risk factors and outcomes after severe traumatic brain injury. (5th December 2016) - Humble, Stephen S.; Wilson, Laura D.; McKenna, John W.; Leath, Taylor C.; Song, Yanna; Davidson, Mario A.; Ehrenfeld, Jesse M.; Guillamondegui, Oscar D.; Pandharipande, Pratik P.; Patel, Mayur B.
Abstract: Objective : To determine risk factors associated with tracheostomy placement after severe traumatic brain injury (TBI) and subsequent outcomes among those who did and did not receive a tracheostomy. Methods : This retrospective cohort study compared adult trauma patients with severe TBI ( n = 583) who did and did not receive tracheostomy. A multivariable logistic regression model assessed the associations between age, sex, race, insurance status, admission GCS, AIS (Head, Face, Chest) and tracheostomy placement. Ordinal logistic regression models assessed tracheostomy's influence on ventilator days and ICU LOS. To limit immortal time bias, Cox proportional hazards models assessed mortality at 1, 3 and 12-months. Results : In this multivariable model, younger age and private insurance were associated with increased probability of tracheostomy. AIS, ISS, GCS, race and sex were not risk factors for tracheostomy placement. Age showed a non-linear relationship with tracheostomy placement; likelihood peaked in the fourth decade and declined with age. Compared to uninsured patients, privately insured patients had an increased probability of receiving a tracheostomy (OR = 1.89 [95% CI = 1.09–3.23]). Mortality was higher in those without tracheostomy placement (HR = 4.92 [95% CI = 3.49–6.93]). Abbreviated injury scale-Head was an independent factor for time to death (HR = 2.53 [95% CI = 2.00–3.19]), but age, gender and insurance were not. Conclusions : Age and insurance status are independently associated with tracheostomy placement, but not with mortality after severe TBI. Tracheostomy placement is associated with increased survival after severe TBI.